Department of Physical Chemistry in M.V. Lomonosov Institute of Fine Chemical Technologies at the RTU MIREA: From the beginning to the present - A. V. Grashkina; V. R. Flid (Тонкие химические технологии)
Objectives. To review the prerequisites for the origin of physical chemistry at the turn of the 19th–20th centuries and to evaluate the contribution of the Department of Physical Chemistry at the M.V. Lomonosov Institute of Fine Chemical Technologies in the development of the main areas of chemical science.Results. The study considers the historical retrospective of the appearance of the Department of Physical Chemistry at the beginning of the 20th century. The main areas of scientific activity over the past 120 years are shown.Conclusions. The Department of Physical Chemistry has made a significant contribution to the formation of physical and chemical knowledge among specialists in wide areas of chemical science and chemical technology. The Department of Physical Chemistry through its pedagogical and scientific activities maintains and expands the areas development, based on the unity of theory and practice, established by its founders. The decisive role of fundamental research in the development of new technologies is also shown.